Бежин луг: избранные рассказы / И. С. Тургенев - Тургенев Иван Сергеевич (Серия "Школьная библиотека", 2017)
Экземпляры: (20190522) / Инвентарный номер: 50334 / Цена: 98.00 / Сис.шифр: 84(2=411.2)1-44 / Авт.знак: Т 87 / ББК: 84(2=411.2)1-44